Immunohistochemical Expression of Basement Membrane Laminin in Histological Grades of Oral Squamous Cell Carcinoma: A Semiquantitative Analysis - Prakhar Mangal; Adarsh Sanikop; Vikas Pandey; Tanushree Satpathy; Ripudaman Sharma; Shilpi Sharma; Dipooja Patil (Journal of Pharmacy and Bioallied Sciences)
Background: Oral squamous cell carcinoma (OSCC) is a prevalent malignancy characterized by varying histological grades. Basement membrane laminin expression plays a crucial role in tumor invasion and progression. This study aimed to assess the immunohistochemical expression of basement membrane laminin in different histological grades of OSCC. Materials and Methods: Archival tissue samples of OSCC from 60 patients were categorized into well-differentiated, moderately differentiated, and poorly differentiated grades. Immunohistochemistry was performed using anti-laminin antibodies, and staining intensity was semiquantitatively analyzed using a scoring system. Results: The immunohistochemical analysis revealed varying levels of laminin expression across different histological grades of OSCC. Well-differentiated tumors showed an average staining intensity score of 7.2 (SD ± 1.5), moderately differentiated tumors had a score of 5.8 (SD ± 1.2), and poorly differentiated tumors exhibited a score of 4.3 (SD ± 0.9). Statistical analysis indicated a significant difference in laminin expression between histological grades (P < 0.001). Conclusion: Our findings demonstrate a progressive decrease in basement membrane laminin expression with an increasing histological grade of OSCC. This suggests that laminin may be a potential biomarker for assessing tumor aggressiveness and prognosis in oral squamous cell carcinoma.